Malnutrition among under-5 children and its determinants in the southwestern coastal region of Bangladesh: A community-based study - Shahinur Akter; Nishana Afrin Nishu (BMJ Open)
Objective The study examines the prevalence of stunting, the most common form of malnutrition and its determinants among children under-5 in the southwestern coastal region of Bangladesh.Design Cross-sectional survey.Settings Two coastal villages of the Bagerhat and Khulna districts of Bangladesh.Participants Participants were selected using the simple random sampling technique with the following criteria: mothers who had at least one under-5 child and resided in the study area for not less than three consecutive years.Outcome measures To assess the nutritional status particularly, stunting (height for age) in children under-5, a standardised anthropometric measurement tool, such as a height-measuring vertical scale, was used and categorised into severely stunted, moderately stunted and normal height.Results The study found that 57.5% of children were severely and 29% were moderately stunted. Findings revealed that mothers’ age, prior experience of under-5 mortality, mothers’ working status and age of the children were significant determinants of stunting prevalence among children under-5. Moreover, children of mothers aged 21–30 years (AOR = 2.190; 95% CI: 1.039 to 4.613; p = 0.039) and children of mothers without prior experience of under-5 mortality (AOR = 4.426; 95% CI: 1.461 to 13.405; p = 0.009) were more possibly to be severely and moderately stunted, respectively. Additionally, children of non-working mothers were more likely to be moderately (AOR = 4.037; 95% CI: 1.382 to 11.792; p = 0.011) and severely stunted (AOR = 2.538; 95% CI: 1.033 to 6.238; p = 0.042). Moreover, children aged ≤24 months (AOR = 0.151; 95% CI: 0.034 to 0.661; p = 0.012) and 25–36 months (AOR = 0.195; 95% CI: 0.046 to 0.829; p = 0.027) were less possibly to be moderately stunted.Conclusion The study recommends training young mothers on effective child-rearing practices, creating income opportunities for women in rural Bangladesh, implementing local awareness programmes about appropriate growth standards for children and expanding facility-based healthcare centres in rural areas for better access to quality healthcare.